COVID-19 Reverse Prediction and Assessment on the Diamond Princess Cruise Ship - Zhang, Juan; Sun, Gui-Quan; Li, Mingtao; Gao, Rui; Ren, Huarong; Pei, Xin; Jin, Zhen (Frontiers in Physics, 2020)
AAs of July 21st, 2020, the new coronavirus (SARS-CoV-2) has infected almost all countries around the world and caused more than 14.8 million confirmed cases, due to its strong transmissibility and fast spread speed. Among these regions,``Diamond Princess" cruise ship is a special infection place, an isolated system with a high population concentration and highly dense space, providing more favorable conditions for the spread of the novel coronavirus pneumonia(COVID-19). In addition, the Japanese government's emergency measures for the spread of COVID-19 on the cruise ship were also being questioned. Therefore, a homogeneous mixed difference system is established in this paper to describe the transmission mechanism of COVID-19 on the cruise ship, to reverse-predict the epidemic transmission trend from January 20 to February 20, 2020, including the daily number of infected human and the peak time of infection, to calculate the range of the basic reproduction number of virus transmission on the cruise ship, and to assess the effect of prevention and control measures. It is concluded that isolation of people, rapid and comprehensive detection play an important role in the control of the epidemic. In fact, the Japanese government's emergency measures have a certain control effect, but the number of infected people would be reduced by at least 60 percent if all personnel on the cruise ship had been tested and placed promptly and quickly as early as February 5.